2022
DOI: 10.3390/jcm11113024
|View full text |Cite
|
Sign up to set email alerts
|

Acute Coronary Syndrome in the COVID-19 Era—Differences and Dilemmas Compared to the Pre-COVID-19 Era

Abstract: The COVID-19 pandemic has led to numerous negative implications for all aspects of society. Although COVID-19 is a predominant lung disease, in 10–30% of cases, it is associated with cardiovascular disease (CVD). The presence of myocardial injury in COVID-19 patients occurs with a frequency between 7–36%. There is growing evidence of the incidence of acute coronary syndrome (ACS) in COVID-19, both due to coronary artery thrombosis and insufficient oxygen supply to the myocardium in conditions of an increased n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 121 publications
0
1
0
Order By: Relevance
“…With additional data, it could be possible to identify factors that could lead to the increased incidence of AMI, with the ultimate goal of a timely diagnostic and early recognition, as well as the education of the population, especially the elderly, about the signs and symptoms of AMI. [14][15][16] This study showed the influence and significance of circadian rhythms and seasonal variations on the incidence of AMI. A higher incidence was observed in the winter months, especially in January, in the early morning hours.…”
Section: Discussionmentioning
confidence: 69%
“…With additional data, it could be possible to identify factors that could lead to the increased incidence of AMI, with the ultimate goal of a timely diagnostic and early recognition, as well as the education of the population, especially the elderly, about the signs and symptoms of AMI. [14][15][16] This study showed the influence and significance of circadian rhythms and seasonal variations on the incidence of AMI. A higher incidence was observed in the winter months, especially in January, in the early morning hours.…”
Section: Discussionmentioning
confidence: 69%
“…When the SARS-CoV-2 virus binds with ACE2 receptors, it leads to the downregulation of these receptors, and this increases the activity of angiotensin II. This mechanism results in systemic vasoconstriction, apoptosis, inflammation, and endothelial proliferation, leading to cardiomyocyte damage or the worsening of previous ischemic condition [27]. Another identified mechanism of acute myocardial infarction in COVID-19 patients is coronary embolism, found in 3% of AMI patients [28].…”
Section: Discussionmentioning
confidence: 99%
“…In case of GCM, there have also been reported cases or an association between this type of myocarditis and infections involving Coxsackie type B and Parvovirus B19 viruses (46,47). Myocardial damage accompanied by elevated hsTnI values is often registered in patients with Covid-19 infection (48). Amiri A. and colleagues described a case of GCM in a patient with Covid-19 infection (49).…”
Section: Histopathological Findings Potential Etiological Factors And...mentioning
confidence: 99%